MOF‐derived/zeolite hybrid catalyst for the production of light olefins from CO2. Issue 22 (11th September 2020) - Martín, Nuria; Portillo, Ander; Ateka, Ainara; Cirujano, Francisco G.; Oar‐Arteta, Lide; Aguayo, Andrés T.; Dusselier, Michiel
Abstract: In this contribution we propose an alternative catalytic system based on MOF derivatives and small pore zeolites for the selective conversion of CO2 into light olefins, using the lowest metal loadings and highest GHSV reported in literature. The catalyst synthesis involves deriving In−Zr oxides from MOFs containing these metals in their structure, i. e. (Zr)UiO‐67‐bipy‐In, via direct calcination in the presence of the zeolite, avoiding co‐precipitation, washing and mixing steps. This effectively creates a truly bifunctional In−Zr zeolite catalyst, opposed to physical mixtures of two catalysts using different precursors. The good dispersion and low loadings of the MOF‐derived In−Zr oxide supplemented with the strong acidity of chabazite‐type zeolites allows to couple the activation of CO2 with C−C coupling, obtaining space time yields of 0.1 mol of CO2 converted to light olefins per gram of In per hour at 375 °C, under the GHSV conditions employed. Abstract : CO2 transformation : In−Zr MOF co‐calcined along with small pore zeolites (i. e. SSZ‐13) is more efficient than the physically mixed (co‐precipitated) In−Zr oxides in the direct transformation of CO2 into light olefins, obtaining 100 mmol of light olefins per gram of In per hour.